CORPORATE GOVERNANCE AND MANAGEMENT OF SMALL AND MEDIUM SCALE ENTERPRISES IN LAGOS – NIGERIA - Chigo, Uchehara, Chris (IJRDO - Journal of Business Management, 2017)
This paper examined corporate governance and the management of SMEs in Lagos state. Corporate governance is not particularly alien to SMEs, hence this study focused on rating respondents perspective in vital areas of corporate governance to an organisation as well as measured its significant effect on accountability and efficiency of operations. The study gathered data by means of a questionnaire from SMEs owners and managers numbering a total of 491 valid participants. Using mean scores, one-sample t-test and regression ANOVA, results were attained and analysed with reference to the hypotheses formulated. The result revealed that good corporate governance was accepted to promote strategic guidance of SMEs for effective monitoring of their environment; and significant factor in improving internal control and efficiency. Though accountability and transparency were identified as important outcome of corporate governance, the regression ANOVA was however not significant. It was thus recommended that greater awareness need to be created in SMEs of the usefulness of giving consideration to the issue of corporate governance in order to earn the dividend therefrom.